A CASH WAQF INVESTMENT MODEL: AN ALTERNATIVE MODEL FOR FINANCING MICRO-ENTERPRISES IN MALAYSIA - Duasa, Jarita; Thaker, Mohamed Asmy Bin Mohd Thas (Journal of Islamic Monetary Economics and Finance, 2016)
This study was designed to empirically determine: (i) to look the factors causes micro enterprises opt for using internal funding instead of external funding; and (ii) to observe the probability of micro enterprises opt for Cash Waqf fund as alternative source of funding their business. The primary data is collected from the administered survey questions in Klang Valley (Selangor and Kuala Lumpur) and the analysis is conducted using statistical analysis and Structural Equation Modeling (SEM). The model is validated its acceptance in the field by adopting the Theory of Reasoned Action (TRA). From the findings, among the factors that lead micro enterprises to use internal funding are strict collateral requirement by commercial financial institutions, high cost of financing, strict documentation requirement and good financial and business track record. Unfortunately, most of them cannot fulfill these conditions and continue to face the problem of accessing finance. The present study has developed the Cash Waqf Investment model to support micro enterprises to improve their access to finance and enhance the skills. Based on the responses received from the field, it has been shown that the intention and readiness of micro enterprises in accepting the model as a source of financial and human capital development services is impressive.